Human Apolipoprotein E4 Alters the Amyloid-β 40:42 Ratio and Promotes the Formation of Cerebral Amyloid Angiopathy in an Amyloid Precursor Protein Transgenic Model - Fryer, John D. (J Neurosci, 2005)
Alzheimer's disease (AD) is characterized by the aggregation and deposition of the normally soluble amyloid-β (Aβ) peptide in the extracellular spaces of the brain as parenchymal plaques and in the walls of cerebral vessels as cerebral amyloid angiopathy (CAA). CAA is a common cause of brain hemorrhage and is found in most patients with AD. As in AD, the ϵ4 allele of the apolipoprotein E (apoE) gene (APOE) is a risk factor for CAA. To determine the effect of human apoE on CAA in vivo, we bred human APOE3 and APOE4 “knock-in” mice to a transgenic mouse model (Tg2576) that develops amyloid plaques as well as CAA. The expression of both human apoE isoforms resulted in a delay in Aβ deposition of several months relative to murine apoE. Tg2576 mice expressing the more fibrillogenic murine apoE develop parenchymal amyloid plaques and CAA by 9 months of age. At 15 months of age, the expression of human apoE4 led to substantial CAA with very few parenchymal plaques, whereas the expression of human apoE3 resulted in almost no CAA or parenchymal plaques. Additionally, young apoE4-expressing mice had an elevated ratio of Aβ 40:42 in brain extracellular pools and a lower 40:42 ratio in CSF, suggesting that apoE4 results in altered clearance and transport of Aβ species within different brain compartments. These findings demonstrate that, once Aβ fibrillogenesis occurs, apoE4 favors the formation of CAA over parenchymal plaques and suggest that molecules or treatments that increase the ratio of Aβ 40:42 may favor the formation of CAA versus parenchymal plaques.